Socialization of the Content Language Integrated Learning (CLIL) Program in Learning - Uyun, Aip Syaepul; Lisnawati, Lisnawati; Salsabila, Anisa Nazwa (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This article discusses the application of the Content and Language Integrated Learning (CLIL) approach to improve English language skills in Indonesia, especially in rural areas. The low level of English proficiency in Indonesia, as reported by Education First (EF), shows that this ability is still a major challenge, especially in schools with limited resources. In the Community Service (PKM) activity carried out at Madrasah Aliyah Arrahman Nasol Cikoneng Ciamis, the CLIL approach was introduced through a seminar to policy makers and teachers, with the aim of improving the effectiveness of English language learning. The PKM method consists of three main stages: initial assessment, seminar implementation, and evaluation. The results of this program show that CLIL, which integrates language learning and academic content, not only increases students' motivation but also creates a supportive learning environment. Thus, CLIL has the potential to be a sustainable learning strategy to overcome barriers to teaching English in rural settings and improve students' English language skills.